UZBEK-RUSSIAN ECONOMIC RELATIONS AND THE IMPACT OF THE RUSSIAN ECONOMIC PERFORMANCE ON UZBEKISTAN’S GROWTH AND FOREIGN TRADE - KAKHAROV, Jahangir (CENTRAL ASIA AND THE CAUCASUS, 2004)
The Russian and Uzbek economies were parts of the single economy for a period of over 100 years. These years resulted in establishment of a complex of deep economic, scientific, cultural, and military links between the two countries.here are well worked out technological and sup-plier-buyer relations between enterprises and, in some cases, the whole branches of the economies of Russia and Uzbekistan. This paper argues that, despite a significant decline in Uzbek-Russian eco-nomic relations after the break-up of the Soviet Union, Uzbekistan’s economic development, to a large extent, is still dependent on the Russian eco-nomic performance. The number of trade and eco-nomic links decreased during the years of independence, but the majority of ties in the complex web of bilateral economic relations were not eradicated.ood macroeconomic performance in Russia influences positively the Uzbek economy. This was especially noticeable in 2001. In conditions of global economic slowdown and a slump in world market prices for Uzbekistan’s main commodities in 2001, the sustainable import demand in Russia and CIS saved the Uzbek economy from severe economic crisis. Part I of the paper highlights the major stag-es in the history of economic relations between the two countries in the years after the collapse of the U.S.S.R. Part II is devoted to analyzing the current status of economic relations. The next part will look at the prospects of the Russian Uzbek economic and political relations in the near future. And finally, Part IV draws conclusions.